Tamar Herzog, Frontiers of Possession: Spain and Portugal in Europe and the Americas, Cambridge, Harvard University Press, 2015, 400 páginas - Morelli, Federica (Universidad Nacional de Quilmes, 2016)
Fil: Morelli, Federica. Università di Torino; Italia.